Effect of bile acid on the cell membrane functionality of lactic acid bacteria for oral administration - Taranto, Maria Pia (2006)
Lactic acid bacteria and other species dwelling in the gut must be tolerant to bile salts. This study sought to determine the effects of the bile salts taurodeoxycholate (TDCA) and deoxycholate (DCA) on Lactobacillus reuteri CRL 1098, a strain of likely probiotic value. When compared to other lactobacilli, L. reuteri showed the highest survival rate but remained sensitive to high (>3 mM) DCA concentrations. DCA produced complete permeabilization of cells, abolished glucose uptake and severely distorted the cell envelope, as shown by electron microscopy. Detailed analytical studies revealed a change in the phospholipid to glycolipid ratio, and also in lipid proportions. The C18:1 W9C form remarkably increased, possibly following a rapid adaptive response during DCA treatment. This study provides the first solid evidence of the mechanism of DCA toxicity in a lactic acid bacterium.